“FREED instils a bit of hope in the eating disorder community… that things can change.”: an investigation of clinician views on implementation facilitators and challenges from the rapid scaling of the First Episode Rapid Early Intervention for Eating Disorders programme - Hyam, Lucy; Yeadon-Ray, Olivia; Richards, Katie; Semple, Amy; Allen, Karina; Owens, Jill; Jackson, Aileen; Semple, Laura; Glennon, Danielle; Di Clemente, Giulia; Griffiths, Jess; Mills, Regan; et al. (Frontiers in Psychiatry, 2024)
Introduction First Episode Rapid Early Intervention for Eating Disorders (FREED) is the leading eating disorder (ED) early intervention model for young people. Research has shown that it reduces the duration of untreated illness, improves clinical outcomes, and has cost savings. However, less is known about the experience of implementing FREED. This study aimed to investigate the views and experiences of adopting, implementing, and sustaining FREED from the perspective of clinical staff. Methods Seven focus groups were conducted involving 26 clinicians. Thematic analysis was used, with the Non-Adoption, Abandonment and Challenges to Scale-up, Spread and Sustainability (The NASSS framework) framework being applied to organise subthemes and determine facilitators and barriers. The NASSS framework was also used to rate the complexity of themes as either simple (straightforward, predictable, few components), complicated (multiple interrelating components), or complex (dynamic, unpredictable, not easily divisible into constituent components). Results There were 16 subthemes identified under seven broader themes representing each domain of the NASSS framework. Key barriers and areas of complexity included factors related to EDs as an illness (e.g., high acuity and prevalence), and organisational complexity (e.g., staffing shortages, lack of managerial/team support). Key facilitators included positive clinician/adopter attitudes, a supportive national network, and the ability for FREED to be flexible/adaptable over time. Conclusion The FREED model appears to be desirable to clinical staff. Wider team and managerial support was perceived to be particularly important to its successful implementation, as were the national network and supervision. Key areas of complexity include staffing issues and high ED acuity/prevalence. These barriers to implementation need to be managed and investment continued to expand and improve early intervention for EDs further.